The great Gatsby - Fitzgerald, F. Scott (Francis Scott), 1896-1940.; Penguin Books (London : Penguin books, 2006)
Jay Gatsby had once loved beautiful, spoiled Daisy Buchanan, then lost her to a rich boy. Now, mysteriously wealthy, he is ready to risk everything to woo her back. This is the definitive, textually accurate edition of a classic of twentieth-century literature, The Great Gatsby. The story of the fabulously wealthy Jay Gatsby and his love for the beautiful Daisy Buchanan has been acclaimed by generations of readers. But the first edition contained a number of errors resulting from Fitzgerald's extensive revisions and a rushed production schedule.
Keywords: First loves -- Fiction; Mistresses -- Fiction; Revenge -- Fiction; Rich people -- Fiction; Traffic accidents -- Fiction; Long Island (N.Y.) -- Fiction; Love stories; Psychological fiction